2020
DOI: 10.23960/jemit.v1i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Data Perubahan Suhu, CO dan CO2 Secara Real Time Menggunakan MySQL

Abstract: This research is related to making a system to display data on temperature changes, CO, and CO2 monitoring results in real time make use of MySQL. The measuring instrument used consisted of an MQ-7 sensor to detect CO gas, a MQ-135 sensor to detect CO2 gas, a DHT-22 sensor to measure the temperature and a microcontroller as a control system. Measurement data is displayed on the PC server using an interface created through the Visual Basic 2010 program and saved to the Mysql database. In this research, a baudra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In this research, the author upgrades the existing monitoring system by incorporating information system technology [3]. This is achieved using open-source applications such as Grafana for data visualization / display [4] - [7], MySQL as a database [8], and Node-Red as a tool to connect sensor data to the computer. PT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the author upgrades the existing monitoring system by incorporating information system technology [3]. This is achieved using open-source applications such as Grafana for data visualization / display [4] - [7], MySQL as a database [8], and Node-Red as a tool to connect sensor data to the computer. PT.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of previous research through a literature review from various journals, it was found that the Node-RED system as the back end and Grafana as the front end are highly recommended to support company management [8] - [9]. This can be observed from several journals, mentioning that Node-RED and Grafana greatly assist companies in visualizing data extracted from real-time object data, such as sensor data, and processing them into information to support decision making.…”
Section: Introductionmentioning
confidence: 99%